2013
DOI: 10.1002/jca.21297
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in bradykinin generation during leukocytapheresis using novel cellsorbaTM CS‐180S: Effects of changing the filling solution

Abstract: We evaluated the bradykinin generation level during leukocytapheresis (LCAP) using novel Cellsorba(TM) CS-180S, which has sodium pyrosulfite and sodium carbonate as a filling solution. Subjects of this study were 14 rheumatoid arthritis patients. Regardless of the type of anticoagulant used, bradykinin levels were lower with the novel CS-180S than with the conventional CS-180S (28.7 ± 53.3 vs. 8.0 ± 2.7 as the mean ± standard deviation). When anticoagulants other than nafamostat mesilate were used with the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, after that, in 2008, the filling solution for Cellsorba column was changed from injection water to sodium pyrosulfite and sodium carbonate. Yamada et al reported that in the Cellsorba column with new filling solution, bradykinin production was suppressed when heparin was used; no bradykinin‐associated ARs were noted. They also reported that the new filling solution may have reduced the amount of negative charge on the nonwoven polyester fiber in the Cellsorba column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after that, in 2008, the filling solution for Cellsorba column was changed from injection water to sodium pyrosulfite and sodium carbonate. Yamada et al reported that in the Cellsorba column with new filling solution, bradykinin production was suppressed when heparin was used; no bradykinin‐associated ARs were noted. They also reported that the new filling solution may have reduced the amount of negative charge on the nonwoven polyester fiber in the Cellsorba column.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there was no statistically significant difference in the incidence of intrafilter pressure increases between the nafamostat mesilate and heparin groups. Yamada et al reported that factor XII, which is activated by negative charge and related to blood coagulation, may be less generated in the Cellsorba column with the new filling solution. This result supports the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…IM‐TR has negatively charged column and filters, and thus, the risk of bradykinin production is high . Bradykinin production could induce adverse events such as hypotension, and the most common complications during IA are bradykinin‐induced hypotension and decreased fibrinogen .…”
Section: Discussionmentioning
confidence: 99%